The role of statins in amyotrophic lateral sclerosis: protective or not? - Al-kuraishy, Hayder M.; Jabir, Majid S.; Sulaiman, Ghassan M.; Mohammed, Hamdoon A.; Al-Gareeb, Ali I.; Albuhadily, Ali K.; Jawad, Sabrean F.; Swelum, Ayman A.; Abomughaid, Mosleh M. (Frontiers in Neuroscience, 2024)
Amyotrophic lateral sclerosis (ALS) is a progressive neurodegenerative disease of motor neurons characterized by muscle weakness, muscle twitching, and muscle wasting. ALS is regarded as the third-most frequent neurodegenerative disease, subsequent to Alzheimer's disease (AD) and Parkinson's disease (PD). The World Health Organization (WHO) in 2007 declared that prolonged use of statins may induce development of ALS-like syndrome and may increase ALS risk. Subsequently, different studies have implicated statins in the pathogenesis of ALS. In contrast, results from preclinical and clinical studies highlighted the protective role of statins against ALS neuropathology. Recently, meta-analyses and systematic reviews illustrated no association between long-term use of statins and ALS risk. These findings highlighted controversial points regarding the effects of statins on ALS pathogenesis and risk. The neuroprotective effects of statins against the development and progression of ALS may be mediated by regulating dyslipidemia and inflammatory changes. However, the mechanism for induction of ALS neuropathology by statins may be related to the dysregulation of liver X receptor signaling (LXR) signaling in the motor neurons and reduction of cholesterol, which has a neuroprotective effect against ALS neuropathology. Nevertheless, the exact role of statins on the pathogenesis of ALS was not fully elucidated. Therefore, this narrative review aims to discuss the role of statins in ALS neuropathology.